2003
DOI: 10.1159/000076284
|View full text |Cite
|
Sign up to set email alerts
|

De novo 9-break-event in one chromosome 21 combined with a microdeletion in 21q22.11 in a mentally retarded boy with short stature

Abstract: We report on a moderately mentally retarded 12-year-old boy of short stature showing the most complex chromosomal rearrangement (CCR) within a single chromosome ever described. A de novo derivative chromosome 21 was recognized in GTG-banding shortly after birth. However, the nature of the rearrangement remained obscure up to the application of the chromosome 21-specific centromere-near multicolor-FISH (subcenM-FISH) probe set and of six selected locus-specific probes along chromosome 21. An unbalanced 9-break-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Since DSB-containing chromosome domains have only limited mobility, chromosome domains in each other's vicinity would be more often involved, and chromosome domains located far apart in the gamete interphase nucleus are less likely to be involved in the same CCR. So in general more breakpoints than chromosomes should be involved in CCRs, an expectation that seems to be confi rmed by this report and other recent high-resolution analysed CCRs (Houge et al, 2003;Weise et al, 2003;de Vries et al, 2005;Gribble et al, 2005;Kuechler et al, 2005;Rosenberg et al, 2005). A single 'catastrophic' event causing multiple chromatin breaks could thus explain the origin of CCRs and other non-recurrent chromosomal aberrations (NRCAs).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Since DSB-containing chromosome domains have only limited mobility, chromosome domains in each other's vicinity would be more often involved, and chromosome domains located far apart in the gamete interphase nucleus are less likely to be involved in the same CCR. So in general more breakpoints than chromosomes should be involved in CCRs, an expectation that seems to be confi rmed by this report and other recent high-resolution analysed CCRs (Houge et al, 2003;Weise et al, 2003;de Vries et al, 2005;Gribble et al, 2005;Kuechler et al, 2005;Rosenberg et al, 2005). A single 'catastrophic' event causing multiple chromatin breaks could thus explain the origin of CCRs and other non-recurrent chromosomal aberrations (NRCAs).…”
Section: Discussionsupporting
confidence: 77%
“…Potential mechanisms generating such complex rearrangements are discussed. Copyright © 2006 S. Karger AG, Basel Complex chromosomal rearrangements (CCRs) have been defi ned as constitutional structural rearrangements involving three or more breakpoints (Houge et al, 2003;Weise et al, 2003). CCRs have been classifi ed based on the inheritance (familial or de novo), the number of breakpoints involved (less or more than four) or the number of chromosomes involved.…”
Section: Patient Reportmentioning
confidence: 99%
“…Patsalis et al [2004] studied 20 families with apparently balanced translocations and found additional, cryptic aberrations in 15%, which reclassified them as CCRs. This probably also holds true for intrachromosomal rearrangements, but to date, only 10 cases have been described [Romain et al, 1985;Tuck-Muller et al, 1996;Van Esch et al, 2002;Weise et al, 2003;Chudoba et al, 2004;Shim et al, 2004;de Vries et al, 2005;Gajecka et al, 2006;Piovani et al, 2006;Thienpont et al, 2006]. We here report on the detailed characterization of an extremely complex intrachromosomal rearrangement of chromosome 1, revealing 14 different breakpoints, 12 on the p-and two on the q-arm as well as a small deletion of 0.5 Mb on the p-arm.…”
mentioning
confidence: 67%
“…They are extremely rare and classified depending on the origin, number of breakpoints (Kousseff et al 1993), or number of chromosomes involved (Kausch et al 1988). More than 120 cases of CCRs have been published (Batanian and Eswara 1998;Houge et al 2003;Weise et al 2003;Patsalis et al 2004;Vermeulen et al 2004). Although most carriers of balanced chromosomal rearrangements are phenotypically normal, in a small proportion ($6%) phenotypic abnormalities have been reported (Warburton 1991).…”
Section: Introductionmentioning
confidence: 99%